Dual-phase effects of emotional music on driving fatigue: delay and awakening revealed by pupillometry - Hu, Zhigang; Li, Kejin; Cui, Yi; Shang, Xianru (Frontiers in Psychology, 2025)
This study investigated the effects of different emotional background music on driving fatigue through a 60-min simulated driving experiment. The research employed a dual-phase design (0–40 min fatigue-delaying phase and post-40 min fatigue-awakening phase) with three auditory conditions: positive music, negative music, and no background music (driving noise only). Pupil diameter variation coefficient and average blink rate were used as objective fatigue evaluation metrics. The results demonstrated that when different emotional background music was introduced before fatigue onset, positive music effectively delayed fatigue development during prolonged driving. Under monotonous driving noise conditions, positive music stimulation administered after fatigue onset significantly improved driver fatigue levels, with the most pronounced awakening effects observed when positive music followed negative music stimulation. These findings indicate that strategically selected positive background music can serve both preventive (delaying fatigue onset) and active (alleviating existing fatigue) functions, providing practical solutions for driver safety and fatigue management.